2010
DOI: 10.1109/tcomm.2010.08.090119
|View full text |Cite
|
Sign up to set email alerts
|

Results on Finite Wireless Networks on a Line

Abstract: Abstract-Today, due to the vast amount of literature on largescale wireless networks, we have a fair understanding of the asymptotic behavior of such networks. However, in real world we have to face finite networks for which the asymptotic results cease to be valid. We refer to networks as being finite when the number of nodes is less than a few hundred. Here we study a model of wireless networks, represented by random geometric graphs. In order to address a wide class of the network's properties, we study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…When R − r v ≥ R a , A is entirely included in v's neighborhood. Thus, E[N] = λπR 2 a , and E[l u ] is given by (14), together leading to (18).…”
Section: Proof Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…When R − r v ≥ R a , A is entirely included in v's neighborhood. Thus, E[N] = λπR 2 a , and E[l u ] is given by (14), together leading to (18).…”
Section: Proof Ofmentioning
confidence: 99%
“…Furthermore, we are interested in studying cascading failures in networks with geometric characteristics such as electrical power grids and wireless communication networks, which could be well-modeled as random geometric graphs. Indeed, random geometric graphs have been widely used in studying wireless networks (see [14] and references therein). As expected, it is shown that geometry plays an important role in quantifying the topology of the smart grid communication and control networks [15].…”
Section: Introductionmentioning
confidence: 99%